2023
DOI: 10.1186/s12933-023-01776-w
|View full text |Cite|
|
Sign up to set email alerts
|

Prediabetes and all-cause mortality in young patients undergoing coronary artery angiography: a multicenter cohort study in China

Abstract: Background The prevalence of prediabetes is increasing in young adults and patients undergoing coronary angiography. However, whether prediabetes is a considerable risk factor for all-cause mortality remains undetermined in young patients undergoing coronary angiography. Methods In this study, we retrospectively included 8868 young patients (men aged < 45 years, women aged < 55 years) who underwent coronary angiography (CAG). Patients were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While more data are needed to confirm this finding, our data could suggest that prediabetes is of greater clinical importance in men than in women, especially in those who are under 65 years. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While more data are needed to confirm this finding, our data could suggest that prediabetes is of greater clinical importance in men than in women, especially in those who are under 65 years. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…While more data are needed to confirm this finding, our data could suggest that prediabetes is of greater clinical importance in men than in women, especially in those who are under 65 years. [26] In the early 2000s, findings from the Diabetes Prevention Program Study showed that metformin reduces the onset of new diabetes in patients with prediabetes, which was believed to be of clinical importance [27]. A 20-year follow-up study, however, confirmed that the treatment of prediabetes with metformin did not translate into improved clinical outcomes, questioning its therapeutic use in prediabetes [28].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study found that pre-DM was present in 36.5% of young patients undergoing CAG. 11 However, only few data are available concerning the prevalence of pre-DM in young patients with CAD. Prediabetes can enhance cardiovascular disease risk by 20% and is related to the increase of incidence of ACS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that pre-DM increased the risk of all-cause death in young individuals undergoing coronary angiography (CAG). 11 However, this association was not significant in those with CAD, acute myocardial infarction (AMI), or undergoing percutaneous coronary intervention (PCI) To date, there is a lack of insight into the relationship between pre-DM and long-term adverse prognosis in young ACS patients. Therefore, this study aimed to examine the impact of pre-DM assessed by FPG or HbA1c levels on the long-term prognosis of patients with new-onset ACS aged≤ 45 years.…”
Section: Introductionmentioning
confidence: 99%